Innovations in service learning: a novel program for community service at NYU School of Medicine - Nola Seta Herlihy; Christina Brown (Medical Education Online, 2015)
Problem: As NYU medical students, the authors determined that there was no structured form of service learning in their curriculum. They sought to establish a service program that recognizes students for their dedication to community service in both the NYU and NYC communities. Approach: In 2012, with the support of the Office of Student Affairs (OSA), the authors created the NYU School of Medicine Community Service Program (CSP). The program tracks and verifies students’ participation in service projects. It sets a goal for students to complete 100 service hours through at least five unique service initiatives. Two reflective essays at the completion of pre-clinical and core clerkship curricula challenge students to express how their service experiences will inform their future careers in medicine. The authors developed an innovative online portal for students to track their service involvement and allow the committee to easily approve hours. They created the Community Service Committee, made up of two representatives from each class year, to be in charge of regulating the program together with the OSA. Outcomes: The class of 2015 is the first class to participate; thus far, 13 students have met program requirements. In the classes of 2016 and 2017, 20 and 41 students, respectively, are expected to receive the award. Total participation has significantly increased in successive class years. Next steps: The authors seek to gather data on CSP participants’ changing perspectives and hope the program can serve as a model for other schools to build service learning into their curricula.